2019
DOI: 10.1039/c8ew00929e
|View full text |Cite
|
Sign up to set email alerts
|

Modelling carbofuran biotransformation byNovosphingobiumsp. KN65.2 in the presence of coincidental carbon and indigenous microbes

Abstract: Interference of coincidental carbon and indigenous bacteria on pesticide removal by biodegrading strains differs in low versus high AOC waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…This was mainly explained by the loss of cell activity due to energy shortages inherent to the oligotrophic target environment. ,, Our results suggest that biotic factors affect both the cell density and activity of MSH1 cells upon introduction in sand filters. As expected, antagonistic sand filter residents were identified that compete for the available resources and hence are expected to further reduce the amount of available energy carriers. ,, Moreover, some residents appear to engage in direct interference competition, further increasing their negative impact. On the other hand, two SFIs increased MSH1’s fitness.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This was mainly explained by the loss of cell activity due to energy shortages inherent to the oligotrophic target environment. ,, Our results suggest that biotic factors affect both the cell density and activity of MSH1 cells upon introduction in sand filters. As expected, antagonistic sand filter residents were identified that compete for the available resources and hence are expected to further reduce the amount of available energy carriers. ,, Moreover, some residents appear to engage in direct interference competition, further increasing their negative impact. On the other hand, two SFIs increased MSH1’s fitness.…”
Section: Discussionmentioning
confidence: 54%
“…As expected, antagonistic sand filter residents were identified that compete for the available resources and hence are expected to further reduce the amount of available energy carriers. 65,79,80 Moreover, some residents appear to engage in direct interference competition, further increasing their negative impact. On the other hand, two SFIs increased MSH1's fitness.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Enhanced growth of the OMP degrader KN65.2 was previously shown on environmental DOM from stagnant ponds and shallow streams. 14 These systems usually contain a larger fraction of labile, low molecular weight DOM compared to other environments, like for instance groundwater. 18,48 Our study showed that KN65.2 can degrade a range of activated monoaromatic phenols, while slightly more refractory, unactivated or diaromatic substrates could not be biodegraded.…”
Section: Discussionmentioning
confidence: 99%
“…Additional carbon sources, occurring for instance in the low molecular weight fraction of DOM, may therefore be important for the survival of OMP degraders due to commonly low OMP concentrations, 25,26 and can, for example, play an import role in bio-augmentation processes. 14,27,28…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation